Pemberdayaan Petani Jagung dalam Mengolah Limbah Tongkol Jagung Empowerment of Corn Farmes in Processing Corn Cob Waste - Sri Adelila Sari; Marini Damanik; Puji Prastowo; Muslim, Muslim; Makhrany Dalimunthe; Feri Yuni Asiyah Kabeakan; Hanisah Hasibuan (Jurnal Pengabdian UntukMu NegeRI, 2024)
Corn cob waste is a problem faced by corn farmers who live in Amplas Village, Dusun I Tambak Rejo, Percut Sei Tuan District, Deli Serdang Regency. This community service project was aimed to provide knowledge and training to the community about processing corn cob waste into organic fertilizer. The people involved were corn farmers those who were named the Reformasi Jaya Farmers Group. The method used was the lecture method by presenting agricultural expert speakers to provide knowledge to farmer groups. Apart from that, training was carried out, where farmer groups were taught and trained about processing corn cobs so that they become organic fertilizer. The results of this activity showed that the farming community was very enthusiastic and enthusiastic. Their knowledge increased by showing that they understood how to prepare fertilizer from processed corn cobs. After the fertilizer was applied to the corn plants, within 5 weeks, it was found that the stems and leaves of the corn plants were growing well. This fertilizer production was also expected to be able to improve the standard of living of farming communities.